Exploring Student’s Perceptions of the Use of English Song in Their Speaking Performance - Kusuma, Angelin; Anggraini, Hesti Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore students' perceptions of the use of English songs, particularly within the RB soul pop genre, in improving their speaking ability. The research focuses on five key aspects of speaking: pronunciation, fluency, vocabulary, comprehension of meaning, and psychological readiness to speak. A qualitative approach with a case study method was employed, involving 59 sixth-semester students of the English Language Education Study Program at Sriwijaya University who had experience learning through songs. Data were collected through open-ended questionnaires and song-based assessments, including lyric completion, reading aloud, and question-and-answer activities related to the song's content. The findings revealed that most students held positive perceptions toward the use of English songs as a medium for speaking practice. Many reported improvements in pronunciation, vocabulary mastery, and fluency, while also highlighting reduced anxiety and increased motivation. However, some challenges were identified, such as difficulty in understanding fast-paced lyrics, unfamiliar accents, and cultural expressions. Overall, English songs proved to be an effective, interactive, and enjoyable learning tool for enhancing students’ speaking performance, provided they are supported by appropriate teaching strategies and sufficient instructional guidance.